Differences in masturbation habits among men and women in Iceland - Katrín Ragnarsdóttir 1991- (2020)
This study examined differences in masturbation habits, including the frequency of masturbation and pornography use, amongst men and women in Iceland. Participants in the study were university students, 18 years of age and older, who answered an anonymous online questionnaire sent to their university email address. A total of 245 students participated; 126 males and 119 females. Most of the participants were married or in a relationship (N = 145) and 91.4% of the participants were heterosexual. For statistical analysis, a t-test, independent samples t-test and a chi-square test was used. The results of this study revealed that there is a difference between men and women when it comes to masturbation habits. Men masturbate much more frequently than women. However, majority of the participants had masturbated at some point in their lives. Keywords: Masturbation, masturbation habits, gender differences, pornography, and sexual pleasure Í þessari rannsókn var skoðaður munur á sjálfsfróunarvenjum, meðal annars tíðni sjálfsfróunar og klám notkun, meðal karla og kvenna á Íslandi. Þátttakendur rannsóknar voru háskólanemar, 18 ára og eldri, sem svöruðu nafnlausri netkönnun sem send hafði verið á háskólanetfang þeirra. Samtals tóku 245 nemendur þátt; 126 karlar og 119 konur. Meirihluti þátttakendanna var kvæntur eða í sambandi (N = 145) og 91.4% þátttakendanna voru gagnkynhneigðir. Fyrir tölfræðilega greiningu voru t-próf, óháð t-próf og kí-kvaðrat próf notuð. Niðurstöður þessarar rannsóknar leiddu í ljós að það er munur meðal karla og kvenna þegar það kemur að sjálfsfróunarvenjum. Karlar stunda mun oftar sjálfsfróun en konur. Hinsvegar, hafði meiri hluti þátttakenda stundað sjálfsfróun á einhverjum tímapunkti í lífinu. Lykilorð: Sjálfsfróun, sjálfsfróunarvenjur, kynjamunur, klám og kynferðisleg ánægja